Subatomic and plural homogeneity as exhaustification effects of different kinds - Paillé, Mathieu (Proceedings of the Amsterdam Colloquium, 2022)
Homogeneity (all-or-nothing) effects are observed in both atoms and pluralities. In this paper, I compare two theories of homogeneity. The first is made for plural homogeneity and the second for subatomic homogeneity, but both capture the effect through existential lexical meaning paired with local exhaustification in positive sentences. I show that neither approach can be extended to the side of the paradigm it was not intended for. But relying on exhaustification for at least subatomic homogeneity is well motivated: all predicates belonging to taxonomies (rather than scales), whether displaying homogeneity effects or not, are interpreted as weak/strong in the same environments, and it is not clear what mechanism other than exhaustification could account for these facts in a united way. Hence, I maintain that homogeneity is an exhaustification effect, and suggest that plural and subatomic homogeneity are simply due to different kinds of local exhaustification.